2021
DOI: 10.15252/embj.2020105043
|View full text |Cite
|
Sign up to set email alerts
|

Tudor staphylococcal nuclease is a docking platform for stress granule components and is essential for SnRK1 activation in Arabidopsis

Abstract: Tudor staphylococcal nuclease (TSN; also known as Tudor‐SN, p100, or SND1) is a multifunctional, evolutionarily conserved regulator of gene expression, exhibiting cytoprotective activity in animals and plants and oncogenic activity in mammals. During stress, TSN stably associates with stress granules (SGs), in a poorly understood process. Here, we show that in the model plant Arabidopsis thaliana, TSN is an intrinsically disordered protein (IDP) acting as a scaffold for a large pool of other IDPs, enriched for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 111 publications
(206 reference statements)
0
42
0
Order By: Relevance
“…Tudor proteins are members of a royal superfamily that also contains the Chromo, MBT, PWWP, and plant Agenet domain proteins [ 28 , 29 ]. Since the first Tudor protein discovered in D. melanogaster [ 30 ], these proteins are also found in mouse, human, zebrafish, yeast, and plants [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Tudor proteins bind to proteins with methylated arginine or lysine residues and take part in cellular processes, such as DNA methylation, RNA metabolism, transcription regulation, DNA damage detection and repair, the P-element-induced wimpy testis (PIWI)-interacting RNA (piRNA) pathway, and the maintenance of genomic stability [ 32 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tudor proteins are members of a royal superfamily that also contains the Chromo, MBT, PWWP, and plant Agenet domain proteins [ 28 , 29 ]. Since the first Tudor protein discovered in D. melanogaster [ 30 ], these proteins are also found in mouse, human, zebrafish, yeast, and plants [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Tudor proteins bind to proteins with methylated arginine or lysine residues and take part in cellular processes, such as DNA methylation, RNA metabolism, transcription regulation, DNA damage detection and repair, the P-element-induced wimpy testis (PIWI)-interacting RNA (piRNA) pathway, and the maintenance of genomic stability [ 32 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…1c), which may lead to increases in their size and number and likely to a change in composition 5 . HS also enhances RNA decapping through the increased association of the mRNA decapping complex DCP1–DCP2 with polysomes 19 . We observed that HS does not significantly affect biotinylation levels of DCP1-TurboID-HF (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TSN is also involved in regulating transcription ( Paukku et al, 2003 ; Yang et al, 2014 ), pre-mRNA splicing ( Yang et al, 2007 ), mRNA stabilization ( Paukku et al, 2008 ), RNA silencing ( Caudy et al, 2003 ), and cleaving hyperedited double-stranded RNA ( Scadden, 2005 ) in animals. Most relevant to the present study, TSN is established with an important role in stress signaling as a docking platform for stress granule proteins and is necessary for assembly and/or function of SGs ( Gao et al, 2015 ; Gutierrez-Beltran et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, TSN functions in mRNA catabolism and links the formation of SGs and processing bodies (PBs)-cytoplasmic RNA granules which are believed to be sites of mRNA degradation ( Arribere et al, 2011 ; Gutierrez-Beltran et al, 2015 ). In the latest study, TSN is established with an important role in stress signaling as a docking platform for stress granule proteins ( Gutierrez-Beltran et al, 2021 ). Therefore, TSN is important for plant development and stress tolerance.…”
Section: Introductionmentioning
confidence: 99%